2015
DOI: 10.1177/1545968315613851
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stroke Type, Locus, and Extent on Long-Term Outcome of Gait Rehabilitation

Abstract: Background Paresis in stroke is largely due to damage to descending corticospinal and corticobulbar pathways. Recovery of paresis predominantly reflects the impact on the neural consequences of this white matter lesion by reactive neuroplasticity (mechanisms involved in spontaneous recovery) and experience-dependent neuroplasticity, driven by therapy and daily experience. However, both theoretical considerations and empirical data suggest that type of stroke (large vessel distribution/lacunar infarction, hemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Leukoaraiosis has been found to predict global functional outcomes in multiple studies 4, 7, 8 but there is paucity of data on domain specific outcomes. 29,31 Our results provide novel insight into this issue by suggesting a domain specific impact of leukoaraiosis on stroke recovery with preexisting leukoaraiosis severity relating to impaired recovery early after stroke predominantly through cognitive impairment.…”
Section: Discussionmentioning
confidence: 78%
“…Leukoaraiosis has been found to predict global functional outcomes in multiple studies 4, 7, 8 but there is paucity of data on domain specific outcomes. 29,31 Our results provide novel insight into this issue by suggesting a domain specific impact of leukoaraiosis on stroke recovery with preexisting leukoaraiosis severity relating to impaired recovery early after stroke predominantly through cognitive impairment.…”
Section: Discussionmentioning
confidence: 78%
“…Evidence in support of this theory comes from recent stroke recovery studies in humans suggesting that deep white matter lesions affecting the corticospinal tract (CST) cause much of the hemiparesis following stroke 26,27 . This evidence was somewhat corroborated by neuroimaging data from patients with lower extremity weakness enrolled in a recent multicenter trial that showed high rates of lacunar infarction 28 . Lesion size may affect motor outcome in those with subcortical stroke 29 .…”
Section: Introductionmentioning
confidence: 73%
“…A directed acyclic graph approach 27 was used to determine which variables would be appropriate to use to adjust for the effects of true aerobic capacity and aid in isolating the distorting effect of motor function on the aerobic capacity measures. Based on the literature, we identified the following potential common causes of both motor dysfunction (lower CGS) and lower aerobic capacity measurement: greater stroke severity, 20,28-30 increased age, 3,31 female sex, 3,31 higher BMI, 3,32,33 depression 34,35 and lower physical activity history. 1,3,20 Hypothesized causal relationships were graphed with unidirectional arrows (Figure 2).…”
Section: Methodsmentioning
confidence: 99%